Acute peripartum pontine ischemic stroke during epidural analgesia - Šklebar, Ivan; Goranović, Tanja; Čerkez Habek, Jasna; Habek, Dubravko (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
We report a rare case of peripartum pontine stroke in a 34-year-old primipara initially attributed to an episode of severe transient hypotension caused by the subdural spread of local anesthetic during epidural analgesia for delivery. The rapid intrapartum intervention by the obstetric team because of spinal shock clinical pictures and fetal bradycardia using high vacuum extraction prevented the risk of fetal ischemic-hypoxic damage. A healthy child was born with an Apgar score of 8/10, 3790 grams /53 cm, with a normal neonatal course. On the third postpartum day, because of persistent neurologic symptoms (headache, urinary, and fecal incontinence), brain magnetic resonance imaging indicated a pontine ischemic lesion. The symptoms gradually regressed with acetylsalicylic acid and physical therapy, and on the 17th day, the patient was discharged home. After puerperium and recovery, thrombophilia were detected. The case indicates the importance of rapid intervention by the obstetric team in case of sudden peripartum maternal and fetal complications.
Keywords: epidural analgeisa; hypotension; fetal hypoxia; pontine stroke; vacuum extraction